There’s Probably a Blackout in Your Television Future: Tracking New Carriage Negotiation Strategies Between Video Content Programmers and Distributors - Frieden, Rob; Jayakar, Krishna; Park, Eun-A (The Columbia Journal of Law & the Arts, 2020)
Video programmers and the satellite and cable operators who distribute their content execute contracts for the mutually profitable offering of services to consumers. However, when programmers and distributors fail to reach closure on new terms and conditions before the end date of an existing agreement, service interruptions (“blackouts”) occur. Video consumers resent having to pay sizable monthly subscriptions for content they temporarily cannot view, and both programmers and distributors risk financial injury. Recognizing the mutual harm to all parties, video programmers and so-called Multichannel Video Programming Distributors (“MVPDs”) usually limit the frequency and duration of blackouts. Heretofore, MVPDs have been able to pass on to subscribers higher programming costs through increased monthly rates without significant declines in subscribership. However, the marketplace for video programming has experienced significant change in recent years, calling into question the continuing ability of MVPDs to raise rates annually at percentages well above measures of general inflation. Additionally, MVPDs have experienced unprecedented declines in subscribership and encountered consumer resentment at having to pay rates, often in excess of $100 monthly, for programming tiers containing dozens of channels, many of which few subscribers have an interest in viewing. Through cord cutting and cord shaving, increasing numbers of video consumers have abandoned an MVPD subscription or downgraded to a less expensive service tier to incur lower monthly rates. Video consumers also have shown greater interest in so-called nonlinear content, available as downloadable files and streaming on demand from new online services, such as Amazon Prime, Hulu, and Netflix, in lieu of conventional live, linear content transmitted by television broadcasters and MVPDs. The marketplace success of nonlinear video content providers demonstrates the growing willingness of consumers to use broadband networks for over-the-top (“OTT”) access to alternative and competitive sources. This Article identifies significant changes in the video marketplace that will trigger more frequent and longer blackouts. The Article will explain how marketplace changes impact the three major sources of video content that MVPDs and broadband networks deliver: (1) broadcast television channels; (2) video content targeted for MVPD subscribers, such as that on CNN, ESPN, and HBO; and (3) video, offered on both a linear and nonlinear basis, by new OTT ventures. For broadcast television, this Article shows how current marketplace conditions challenge the ongoing viability of a legislatively crafted compromise that accords broadcasters the option of electing mandatory carriage of their signal by MVPDs (the “must-carry” requirement) in lieu of contractual “retransmission consent” negotiations. Broadcasters secure guaranteed carriage via MVPDs, and MVPDs benefit by the conferral of a low-cost copyright license to use broadcasters’ content. For competing nonbroadcast video content, MVPDs and the manufacturers of devices, such as Roku, which transfer broadband video content to television sets via broadband networks, negotiate both copyright licenses and delivery rights directly with video programmers. This group also faces market volatility due to changes in consumer preferences and the growing array of video content options available. The Article seeks to answer whether video programmers or MVPDs have overestimated their own negotiating leverage and, in turn, their ability to secure favorable contractual terms and conditions. Broadcasters historically appear to have greater leverage, because they have exclusive control over live, “must-see,” linear content, such as sporting events. This advantage has motivated most broadcasters to eschew the must-carry option and elect retransmission consent negotiations. The Article suggests that a significant increase in blackouts has resulted from reduced opportunities for MVPDs to raise subscription rates without triggering substantial increases in subscriber migration to other broadband-delivered program options. The Article notes that vertically and horizontally integrated MVPDs, such as AT&T and Comcast, are better situated to tolerate more frequent and lengthy blackouts. These companies can offset the adverse financial impact of MVPD subscriber churn with blackout-free alternatives, increased subscribership of their broadband services and unregulated bundling of services and content for subscribers willing to upgrade and pay a higher monthly fee. The Article closely examines a recent antitrust enforcement case that approved AT&T’s acquisition of Time Warner, with an eye toward determining whether reviewing courts understood shifting marketplace conditions that affect the likelihood for more and longer blackouts. The Article concludes that in the AT&T case, both the district and appellate courts woefully underappreciated the ability of this widely diversified venture to trigger and tolerate more blackouts in its capacity as an MVPD and broadband access provider, separate and apart from its capacity as the new owner of Time Warner’s “must-see” CNN and HBO content. The courts concluded that AT&T, having largely abandoned its leverage over access to the Time Warner video content, lacked the ability to trigger blackouts. The courts emphasized the long-term carriage agreements Time Warner had previously negotiated with unaffiliated MVPDs and AT&T’s offer to maintain content access during arbitration of disputes occurring for seven years after merger approval. The courts failed to recognize the significant harm AT&T, in its capacity as a major national MVPD, could inflict on competition and consumers by increasing its use of blackouts for negotiating leverage.